Taxonomic assessment of the Oxytropis species from South-East of Kazakhstan - S. Almerekova; S. Abugalieva; N. Mukhitdinov (Вавиловский журнал генетики и селекции)
The genus Oxytropis DC. is one of the largest genera in the Fabaceae family. The most plant species belonging to the Oxytropis genus have an important medicinal value. Currently the botanical taxonomy of the genus is complicated due to existence of many subgenera and sections that developed based on morphological traits. Also, in the literature there is luck of knowledge on phylogeny of Oxytropis species from Central Asian region. Therefore, the purpose of the present study was the clarification of taxonomic relationship of two Oxytropis species from SouthEast of Kazakhstan (O. almaatensis Bajt. and O. glabra DC.). The study was based on using phylogenetic analysis and haplotype network assessment based on sequences ITS (internal transcribed spacers), which is DNA marker of nuclear genome. Plant materials of O. almaatensis were collected from 2 populations in two neighboring Gorges in Trans Ili Alatau Mountains, O. glabra plant material was obtained from Herbarium of the Department of Biodiversity and Bioresources, al-Farabi Kazakh National University. Based on DNA sequences of ITS the phylogenetic and network relationships were investigated by using Neighbor Joining and Median Joining methods, respectively. The nucleotide sequences of ITS of O. almaatensis and O. glabra were aligned with sequences of 29 Oxytropis references found in the NCBI database. Out of the 601 aligned positions of ITS 33 (5.6 %) sites were found to be polymorphic nucleotides and used in evaluation of the genetic relationship of species. Constructed MJ haplotype network showed a very high congruence with the NJ phylogenetic tree. MJ network provided valuable additional hints in clarification of the taxonomic relationship among species involved in the analysis. In this study phylogenetic NJ tree and MJ network based on the variation of ITS sequences confirmed the monophyletic origin of the genus. The ITS haplotype network suggested that O. glabra is very diverse species and possibly played important role in the evolutionary processes of the genus in Central Asian region. The study is additional contribution in the molecular taxonomy of complex Oxytropis genus.